Photosynthetic performance in cyanobacteria with increased sulphide tolerance: an analysis comparing wild-type and experimentally derived strains - Martín-Clemente, Elena; Melero-Jiménez, Ignacio José; Bañares-España, Elena; Flores-Moya, Antonio; García-Sánchez, María Jesús (Springer, 2021)
Sulphide is proposed to have influenced the evolution of primary stages of oxygenic photosynthesis in cyanobacteria. However, sulphide is toxic to most of the species of this phylum, except for some sulphide-tolerant species showing various sulphide-resistance mechanisms. In a previous study, we found that this tolerance can be induced by environmental sulphidic conditions, in which two experimentally derived strains with an enhanced tolerance to sulphide were obtained from Microcystis aeruginosa, a sensitive species, and Oscillatoria, a sulphide-tolerant genus. We have now analysed the photosynthetic performance of the wild-type and derived strains in the presence of sulphide to shed light on the characteristics underlying the increased tolerance. We checked whether the sulphide tolerance was a result of higher PSII sulphide resistance and/or the induction of sulphide-dependent anoxygenic photosynthesis. We observed that growth, maximum quantum yield, maximum electron transport rate and photosynthetic efficiency in the presence of sulphide were less affected in the derived strains compared to their wild-type counterparts. Nevertheless, in 14C photoincoporation assays, neither Oscillatoria nor M. aeruginosa exhibited anoxygenic photosynthesis using sulphide as an electron donor. On the other hand, the content of photosynthetic pigments in the derived strains was different to that observed in the wild-type strains. Thus, an enhanced PSII sulphide resistance appears to be behind the increased sulphide tolerance displayed by the experimentally derived strains, as observed in most natural sulphide-tolerant cyanobacterial strains. However, other changes in the photosynthetic machinery cannot be excluded.
Keywords: Fotosíntesis; Microcystis aeruginosa; Oscillatoria; Cyanobacteria; Sulphide resistance; Photosynthesis